Dimensional Accuracy and Tearing Strength of Alginate Impression Material Containing Different Concentrations of Natural Miswak Powder: An In-Vitro Study (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
Background:Alginate impression material is an irreversible hydrocolloid due to its chemical setting reaction. Hydrocolloids dimensional stability depends on the presence of water, as water makes up around 70% of dental alginate. One of the Salvadoraceae families, Salvadora persica, is the source of miswak. The Arak tree, or Salvadora persica, is often referred to as the "toothbrush tree" as it is known in English. It is evergreen form develops like a shrub or small tree with a twisted trunk. The researchers mixed miswak powder with the alginate to examine the dimensional accuracy and tearing strength.Materials and Methods:Sixty alginate specimens were prepared. 30 specimens for dimensional accuracy and 30 specimens for tearing strength, each of them is divided into three groups: The control group, Group A % 17 miswak powder, and Group B % 34 miswak powder. The dimensional stability and tearing strength were tested.Results:There is no dimensional change in group B, lesser dimensional change was revealed in group A, according to control group. Group B is more resistant to tearing strength when compared with the control group and group A, and group A is more resistant than the control group.Conclusion:Adding a suitable amount of miswak powder to alginate is beneficial for reducing and preventing shrinkage, as well as improving tearing strength.